Seismic Design of Bolted Connections in Steel Structures—A Critical Assessment of Practice and Research - Tiago Ribeiro; Luís Bernardo; Ricardo Carrazedo; Dario De Domenico (Buildings, 2022)
The importance of connections in steel structures is paramount, not only because it greatly influences the cost of construction and provides room for innovations, but also due to the connections’ impact on global structural behaviour. Therefore, research into innovative connections for seismic applications and related design criteria has significantly grown in recent years. However, it has been pursued mostly on local—connection or frame—levels, leaving the system analysis and code compliance levels with a meagre investigation. Moreover, less than 1% of published papers concerning steel connections and earthquake engineering are review articles. To overcome this gap, this systematic review of more than 240 references, including scientific contributions and design codes in the field aimed to cover both recent research and current shortcomings in practice and regulations. It has been found that European design rules updated to a fully performance-based design philosophy is imminent and is deemed to bring pre-qualified joints and increased complexity. Design rules have been systematized, and current hindrances have been highlighted. A deeper look into research needs and trends showed that investigations in connections for concentrically X braced frames are still a necessity, while developments in self-centring and replaceable connections as well as in simple solutions for increasing damping are expected to modify how joints are designed, as soon as semi-rigid and partial strength connections are more easily allowed by design codes.